p68 RNA helicase: identification of a nucleolar form and cloning of related genes containing a conserved intron in yeasts. - Iggo, R D (1991)
The human p68 protein is an RNA-dependent ATPase and RNA helicase which was first identified because of its immunological cross-reaction with a viral RNA helicase, simian virus 40 large T antigen. It belongs to a recently discovered family of proteins (DEAD box proteins) that share extensive regions of amino acid sequence homology, are ubiquitous in living organisms, and are involved in many aspects of RNA metabolism, including splicing, translation, and ribosome assembly. We have shown by immunofluorescent microscopy that mammalian p68, which is excluded from the nucleoli during interphase, translocates to prenucleolar bodies during telophase. We have cloned 55% identical genes from both Schizosaccharomyces pombe and Saccharomyces cerevisiae and shown that they are essential in both yeasts. The human and yeast genes contain a large intron whose position has been precisely conserved. In S. cerevisiae, the intron is unusual both because of its size and because of its location near the 3' end of the gene. We discuss possible functional roles for such an unusual intron in an RNA helicase gene.